Complication of Menstrual Regulation (MR)-A Study On It’s Clinical Presentation And Outcome - Jahan, Arshad; Begum, Fatema; Parvin, Mst Tahmina; Begum, Farjana; haque, Muhammad Enamul; Hossain, AZM Zahid (KYAMC Journal, 2021)
Background: Menstrual regulation is the aspiration of endometrial content within 14 days from the missed period or within 42 days from the last menstrual period having previous normal cycles. So embryonic implantation either can not occur or can not be maintained.This technique is also known as menstrual aspiration, menstrual extraction, interception and uterine aspiration.This technique was first developed in 1927. In spite of its safety and effectiveness, to some extent it is contributory to some minor and major complications. Objective: The aim of this study was to determine the clinical presentation and outcome of the complication of menstrual regulation (MR). Materials and Methods:This cross sectional prospective study was done in Obs.&Gynae department of Dhaka Medical College Hospital, from November 2008 to February 2009. This study was on MR complications, it's clinical presentation and outcome. The cases diagnosed by history, examination and investigation. Results: Total number of Gynaecology admission was 1680 out of which 5.71% was due to MR complications . 89.58 % were multipara . In 77.07% cases gestational age was between 7 to 9 wks, in 52.08% cases MR was performed in private chamber. 12.5% patients suffered from p/v bleeding,2.08% suffered from shock and acute abdomen due to visceral injury. In 9.37% cases required abdominal surgery . Death was recorded in 2.08% cases. Conclusion: To reduce the incidence of complications, contraceptive practice should be popular and available to the community and MR service should be used as back up service when needed. KYAMC Journal Vol. 11, No.-4, January 2021, Page 208-211